Cordyceps militaris induces apoptosis in ovarian cancer cells through TNF-α/TNFR1-mediated inhibition of NF-κB phosphorylation - Eunbi Jo; Hyun-Jin Jang; Kyeong Eun Yang; Min Su Jang; Yang Hoon Huh; Hwa-Seung Yoo; Jun Soo Park; Ik-Soon Jang; Soo Jung Park (BMC, 2020)
Abstract Background Cordyceps militaris (L.) Fr. (C. militaris) exhibits pharmacological activities, including antitumor properties, through the regulation of the nuclear factor kappa B (NF-κB) signaling. Tumor Necrosis Factor (TNF) and TNF-α modulates cell survival and apoptosis through NF- κB signaling. However, the mechanism underlying its mode of action on the NF-κB pathway is unclear. Methods Here, we analyzed the effect of C. militaris extract (CME) on the proliferation of ovarian cancer cells by confirming viability, morphological changes, migration assay. Additionally, CME induced apoptosis was determined by apoptosis assay and apoptotic body formation under TEM. The mechanisms of CME were determined through microarray, immunoblotting and immunocytochemistry. Results CME reduced the viability of cells in a dose-dependent manner and induced morphological changes. We confirmed the decrease in the migration activity of SKOV-3 cells after treatment with CME and the consequent induction of apoptosis. Immunoblotting results showed that the CME-mediated upregulation of tumor necrosis factor receptor 1 (TNFR1) expression induced apoptosis of SKOV-3 cells via the serial activation of caspases. Moreover, CME negatively modulated NF-κB activation via TNFR expression, suggestive of the activation of the extrinsic apoptotic pathway. The binding of TNF-α to TNFR results in the disassociation of IκB from NF-κB and the subsequent translocation of the active NF-κB to the nucleus. CME clearly suppressed NF-κB translocation induced by interleukin (IL-1β) from the cytosol into the nucleus. The decrease in the expression levels of B cell lymphoma (Bcl)-xL and Bcl-2 led to a marked increase in cell apoptosis. Conclusion These results suggest that C. militaris inhibited ovarian cancer cell proliferation, survival, and migration, possibly through the coordination between TNF-α/TNFR1 signaling and NF-κB activation. Taken together, our findings provide a new insight into a novel treatment strategy for ovarian cancer using C. militaris.